Bacterial Interference With Lactate Dehydrogenase Assay Leads to an Underestimation of Cytotoxicity - Van den Bossche, Sara; Vandeplassche, Eva; Ostyn, Lisa; Coenye, Tom; Crabbé, Aurélie (Frontiers in Cellular and Infection Microbiology, 2020)
Models to study host-pathogen interactions in vitro are an important tool for investigating the infectious disease process and evaluating the efficacy of antimicrobial compounds. In these models, the viability of mammalian cells is often determined using the lactate dehydrogenase (LDH) cytotoxicity assay. In the present study we evaluated whether bacteria could interfere with the LDH assay. As a model for host-pathogen interactions, we co-cultured lung epithelial cells with eight bacteria encountered in the lower respiratory tract. We show that LDH activity is affected by Pseudomonas aeruginosa, Klebsiella pneumoniae, Stenotrophomonas maltophilia and Streptococcus pneumoniae, and that this depends on the density of the start inoculum and the duration of infection. Two different mechanisms were discovered through which bacteria interfered with LDH activity, i.e. acidification of the cell culture medium (by K. pneumoniae and S. pneumoniae) and protease production (by P. aeruginosa and S. maltophilia). In addition, we developed and validated a modified protocol to evaluate cytotoxicity using the LDH assay, where bacterial interference with LDH quantification is avoided.